Metatrends in Mobility: Education Hubs and the New Multipolar Structure of International Student Mobility - Glass, Chris; Cruz, Natalie (International Higher Education, 2023)
A network analysis of UNESCO student mobility data from 210 countries over a 20-year period (2000–2019) indicates long-term structural shifts in the shape of international student mobility, with a more diverse set of core countries exerting influence.